2008
DOI: 10.1029/2006jc003994
|View full text |Cite
|
Sign up to set email alerts
|

Physical mechanisms for the offshore detachment of the Changjiang Diluted Water in the East China Sea

Abstract: [1] Physical mechanisms for the summertime offshore detachment of the Changjiang Diluted Water (CDW) into the East China Sea are examined using the high-resolution, unstructured-grid, Finite-Volume Coastal Ocean Model (FVCOM). The model results suggest that isolated low salinity water lens detected west of Cheju Island can be formed by (1) a large-scale adjustment of the flow field to the Changjiang discharge and (2) the detachment of anticyclonic eddies as a result of baroclinic instability of the CDW front. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
120
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(133 citation statements)
references
References 26 publications
7
120
1
Order By: Relevance
“…SeaWiFS-derived salinity images also reveal the source and extent of these low salinity waters that appear to be displaced north of the YR mouth and adopt a nearly linear pattern corresponding with the broad ECS shelf (7 April 1999 as a good example). These results are closely consistent with previous shipboard observations of the surface salinity in the ECS and modeling studies (Chen at al., 2006(Chen at al., , 2008. The contributions of high CDOM concentrations and hence lower salinities are also noted on occasions in the central part of the YS because of the seaward spreading of the LSW plume during the late April-summer (e.g.…”
Section: Implementation To Seawifs Ocean Colour Imagerymentioning
confidence: 99%
“…SeaWiFS-derived salinity images also reveal the source and extent of these low salinity waters that appear to be displaced north of the YR mouth and adopt a nearly linear pattern corresponding with the broad ECS shelf (7 April 1999 as a good example). These results are closely consistent with previous shipboard observations of the surface salinity in the ECS and modeling studies (Chen at al., 2006(Chen at al., , 2008. The contributions of high CDOM concentrations and hence lower salinities are also noted on occasions in the central part of the YS because of the seaward spreading of the LSW plume during the late April-summer (e.g.…”
Section: Implementation To Seawifs Ocean Colour Imagerymentioning
confidence: 99%
“…The Asian monsoon, which is southerly during summer, enhances the northeastward flow of the CDW plume. The CDW, the warm currents, and the southerly monsoon are dominant factors affecting the summer circulation in the ECS (e.g., Chao 1991;Chang and Isobe 2003;Liu et al 2003;Chen et al 2008). The CDW plume spreads out widely on the ECS shelf, and satellite observations provide a useful method for monitoring its variation.…”
Section: Introductionmentioning
confidence: 99%
“…5a, the water column over the slope region is nearly homogeneous, showing that strong tidal mixing occurs there. The model horizontal resolution used in this study may not be sufficient to resolve eddy formation via baroclinic instability, as pointed out by Chen et al (2008). Nevertheless, the large low-salinity patch is reproduced in our simulation, suggesting that the necessary condition is not the small-scale eddy due to baroclinic instability but the tide-induced vertical mixing with the wind-driven cross-isobath transport for the formation of the isolated large low-salinity lens structure.…”
Section: Low-salinity Water Detached From Main Cdw Plumementioning
confidence: 65%
“…Previous modeling studies of the CDW described the effects of wind and ambient current, and suggested that the spreading of freshwater is closely associated with the winddriven surface flow and ambient along-shelf current (Bang and Lie 1999;Chang and Isobe 2003;Chen et al 2008;Moon et al 2009a). Chang and Isobe (2003) emphasized the effect of advection due to along-shelf current between the Taiwan Strait and the Korea Strait, and also suggested that wind effect is non-negligible.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation